Cues-Pause-Point Method to Decrease Immediate Echolalia In Adolescents With Autism - Nastiti, Dina; Mulyo Handayani, Muryantinah (KnE Social Sciences, 2025)
Adolescents with autism who show immediate echolalia may experience a communication disorder that increases the likelihood of social failure. This study aims to decrease immediate echolalia in adolescents with autistic spectrum disorder using the Cues-Pause-Point method. This experiment uses multiple baseline designs across content. The participants were 18-year-old and 19-year-old adolescents with autism who were given verbal questions from three content areas: identification, interaction, and facts. The Cues-Pause-Point method was designed to (a) to encourage the participants to remain quiet before, during, and after the presentation of the question and (b) to teach the participants to use environmental cues, which are response cards placed on the table. Their responses were noted and scored by two observers. The resulting data were analyzed using descriptive visual analysis and showed a decrease in the participants’ echolalia percentage. The results show a trend line decrease of immediate echolalia after all subjects get Cues-Pause-Point treatment.